The pseudophosphatase STYX targets the F‐box of FBXW7 and inhibits SCFFBXW7 function. (22nd December 2016) - Reiterer, Veronika; Figueras‐Puig, Cristina; Le Guerroue, Francois; Confalonieri, Stefano; Vecchi, Manuela; Jalapothu, Dasaradha; Kanse, Sandip M; Deshaies, Raymond J; Di Fiore, Pier Paolo; Behrends, Christian; Farhan, Hesso
Abstract: The F‐box protein FBXW7 is the substrate‐recruiting subunit of an SCF ubiquitin ligase and a major tumor‐suppressor protein that is altered in several human malignancies. Loss of function of FBXW7 results in the stabilization of numerous proteins that orchestrate cell proliferation and survival. Little is known about proteins that directly regulate the function of this protein. In the current work, we have mapped the interactome of the enigmatic pseudophosphatase STYX. We reasoned that a catalytically inactive phosphatase might have adopted novel mechanisms of action. The STYX interactome contained several F‐box proteins, including FBXW7. We show that STYX binds to the F‐box domain of FBXW7 and disables its recruitment into the SCF complex. Therefore, STYX acts as a direct inhibitor of FBXW7, affecting the cellular levels of its substrates. Furthermore, we find that levels of STYX and FBXW7 are anti‐correlated in breast cancer patients, which affects disease prognosis. We propose the STYX–FBXW7 interaction as a promising drug target for future investigations. Synopsis: Mapping the interactome of the enigmatic pseudophosphatase STYX reveals it as a potentially general new regulator of SCF‐type cullin–RING ubiquitin ligases, which stabilizes substrates by blocking recruitment of F‐box‐containing adaptors. Mass spectrometry identifies several F‐box proteins as STYX interactors. STYX competes with the SCF subunit SKP1 for binding to the F‐box domain of FBXW7. STYX negatively regulates FBXW7 function and stabilizes FBXW7 substrates. High STYX and low FBXW7 levels correlate with poor relapse‐free survival of breast cancer patients. Abstract : STYX‐mediated stabilization of ubiquitination targets by blocking substrate adaptor recruitment into SCF E3s may represent a general new mode of cullin–RING ligase regulation.